CSNK1A1 mutations and gene expression analysis in myelodysplastic syndromes with del(5q). (18th June 2015) - Bello, Erica; Pellagatti, Andrea; Shaw, Jacqueline; Mecucci, Cristina; Kušec, Rajko; Killick, Sally; Giagounidis, Aristoteles; Raynaud, Sophie; Calasanz, María J.; Fenaux, Pierre; Boultwood, Jacqueline
Summary Mutations of CSNK1A1, a gene mapping to the commonly deleted region of the 5q‐ syndrome, have been recently described in patients with del(5q) myelodysplastic syndromes (MDS). Haploinsufficiency of Csnk1a1 in mice has been shown to result in β‐catenin activation and expansion of haematopoietic stem cells (HSC). We have screened a large cohort of 104 del(5q) MDS patients and have identified mutations of CSNK1A1 in five cases (approximately 5%). We have shown up‐regulation of β‐catenin target genes in the HSC of patients with del(5q) MDS. Our data further support a central role of CSNK1A1 in the pathogenesis of MDS with del(5q).